Medosebni stik med učiteljem in študenti - Bardorfer, Ana (Psihološka obzorja (Ljubljana), 2013)
Various definitions of rapport can be found between different disciplines and also within a certain discipline, including higher education. Effective teaching is a challenging task and requires a skilled teacher. In addition to managing a variety of didactic and pedagogical approaches, teacher should also be able to create a positive learning environment, including creating a good rapport with his/her students. Unfortunately, numerous imprecise definitions of student-teacher rapport in higher education, usually taken from dictionaries, are used by researchers in this field. We belive this is the reason why they dont provide possibilities for clear operationalization and development of a proper instrument for measuring the quality of student-teacher rapport. In this paper we proposed a new conceptualization of student-teacher rapport in higher education, built on the existing model of general rapport and on the basis of relevant findings from the field of higher education. We defined rapport as an interactive phenomena and placed the emphasis on the subjective experience/insiders perspective, although the quality of rapport can also be estimated through various verbal and non-verbal clues. This experiental aspect is expressed in feelings and thoughts of interactants. Since the teacher acts as a leader of the teaching/learning process he/she is responsable for creating good rapport with his/her students. In the proposed conceptualization we've used same structural components as L. Tickle-Degnen and Rosenthal (1990) used in their model of rapport and adapted them for the context of higher education. These are positivity, mutual attention and coordination. Looking at the existing concepts of student-teacher rapport in higher education through the prism of the aforementioned model, it can be seen that all elements relate either to positivity or mutual attention, while the component of coordination is almost completely absent. In our opinion, it is coordination which differentiates rapport from a general good interpersonal relationship. With coordination we refer to coordinated and smooth interaction and also to coordination in the process of teaching and learning.The new conceptualization of student-teacher rapport in higher education represents an important step toward student-oriented approach to teaching and learning a current paradigm in education in general. Questions which remain open are presented anddirections for further research outlined. Keywords: higher education, teacher student
Keywords: higher education; visokošolsko izobraževanje; odnos med učitelji in študenti; teacher student interaction; medosebni stik; experiental aspect